1993
DOI: 10.1093/carcin/14.5.833
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mutations in human immortalized epithelial cell lines

Abstract: Although rodent cells have been immortalized following transfection with a mutant p53 gene, the role of p53 in the immortalization of human cells is unknown. Therefore, human epithelial cell lines were examined for p53 mutations in exons 4-9 which include the evolutionarily conserved regions. A spontaneously immortalized skin keratinocyte cell line, HaCat, and three ras-transfected clones, have a p53 mutational spectrum that is typical of ultraviolet light induced mutations. A normal finite lifespan cell strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
322
1
10

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(358 citation statements)
references
References 0 publications
25
322
1
10
Order By: Relevance
“…UVA irradiation induces DNA damage also in normal human keratinocytes Since the immortal HaCaT keratinocytes harbor p53 mutations (Lehman et al, 1993) which could influence the UVA-dependent damage response, we next investigated normal human skin keratinocytes. G 1 -enriched keratinocytes (Supplementary Figures 3C and D) were irradiated with 60 J/cm 2 UVA and analysed for g-H2AX foci formation directly after irradiation (0 h) as well as after 10, 20, 30, 60 and 360 min (Figure 5a).…”
Section: Uva Induces Double Strand Breaks In Hacat Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…UVA irradiation induces DNA damage also in normal human keratinocytes Since the immortal HaCaT keratinocytes harbor p53 mutations (Lehman et al, 1993) which could influence the UVA-dependent damage response, we next investigated normal human skin keratinocytes. G 1 -enriched keratinocytes (Supplementary Figures 3C and D) were irradiated with 60 J/cm 2 UVA and analysed for g-H2AX foci formation directly after irradiation (0 h) as well as after 10, 20, 30, 60 and 360 min (Figure 5a).…”
Section: Uva Induces Double Strand Breaks In Hacat Keratinocytesmentioning
confidence: 99%
“…These cells represent an early stage of skin carcinogenesis because they harbor UVB type-specific p53 mutations (Lehman et al, 1993) as well as some chromosomal abnormalities typical for human skin SCCs (Lehman et al, 1993;Boukamp et al, 1997;Popp et al, 2002). While the HaCaT cells remained nontumorigenic through long-term passaging, they became tumorigenic by transduction with the Harvey-ras oncogene, increased temperature or stroma modulating growth factors known to be relevant for tumorigenicity (Boukamp et al, 1990b(Boukamp et al, , 1995(Boukamp et al, , 1997Skobe and Fusenig, 1998;Obermueller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In these two cases, already after infection with 10 PFU's per cell all cells stained positive for b-galactosidase. By contrast to these two highly infective cell lines the keratinocyte cell line HACAT, also expressing mutant p53 (Lehman et al, 1993), showed a very low infectivity. Even after infection with a MOI of 1000 PFU's per cell only a part of the cells stained positive.…”
Section: Infectivity Of DI Erent Human Cell Typesmentioning
confidence: 76%
“…However, Lehman et al, (1993) had previously sequenced the highly conserved region of p53 known as the mutational hot-spot region (exons 4 ± 9) in HMEC184, HMEC184A1 and HMEC184B5 and found a wildtype p53 sequence. However, p53 mutations have been found outside of the hot-spot region in some breast cancers (Hartmann et al, 1995).…”
Section: Hmec184 Contain Wild-type P53mentioning
confidence: 99%